AVALIAÇÃO DO TEOR DE COMPOSTOS FENÓLICOS E ATIVIDADE ANTIOXIDANTE EM MAÇÃS E SEUS PRODUTOS - Zardo, Danianni Marinho (2007)
The apple consumption can contribute in the improvement of the health and well-being by reducing the risk the diseases such as cancer, asthma, diabetes type II and cardiovascular diseases. Scientific evidences indicate that the polyphenols, compounds with high antioxidant activity, are the responsible for this effect. These compounds can vary between varieties, in function of the climate and the cultural treatments. In Brazil little was researched in relation to these constituent in apples, this study presents in one first moment, the analysis of different varieties, considering the whole fruit and their parts, with elaboration of a classification with low and high values. The biggest phenol concentration and antioxidant activity was found in the epicarp. In varieties with different intensities of red pigmentation, the phenolics compounds content was similar, however the antioxidant potential was different. In one second moment the evaluation occurred during the juice and apple wine processing and the responsible factors for the loss of phenols were the enzymatic oxidation and the despectinization. The third moment was reserved for the apple pomace flour that presented high content of polyphenols and antioxidant activity. The results of this study demonstrate that Brazilian apples are fruits with high antioxidant activity. Moreover, apple products can be potent antioxidant sources, since that inhibit the browning enzymatic reaction.